Analisis Strategi Kreatif Pada Iklan Pocari Sweat Ramadhan Oleh Fadil Jaidi Dan Pak Muh 2025 - Hesti Munira; Amelia Zahara; Mukhsin Patriansah (VisArt: Jurnal Seni Rupa dan Design, 2026)
This study analyzes the Creative strategy employed in the 2025 Ramadan advertisement of Pocari Sweat featuring influencer Fadil Jaidi and his father, Pak Muh, produced by Dentsu Creative Indonesia. The advertisement, entitled “Cairan Tubuh Bocor, Emang Bikin Horor” (Leaking Body Fluids Is Truly Horrifying), adopts a horror-comedy approach that has rarely been utilized in Ramadan-themed advertising in Indonesia. This research employs a qualitative descriptive method with a descriptive approach. The analysis begins with a description of the advertising elements, including the advertiser, message, media, target audience, and consumer response. Furthermore, the study examines the visual and verbal messages contained in the advertisement and applies the AIDA model as the analytical framework. The findings indicate that the use of horror genre parody combined with familiar influencer figures successfully generated high audience attention, achieving 108 million views and 659,000 engagements across various digital platforms within one week of its release. The advertising message is delivered through humor and cultural references that reinforce the brand positioning of “Ion Tahan Bocor” (Leak-Proof Ions). The study concludes that a Creative disruption strategy through the combination of genre blending and influencer marketing is effective in increasing brand awareness and consumer purchase intention during the Ramadan period